Réponses

2014-04-09T13:24:39+02:00
Bonjour

a) 5(x+2)=2x+(x+6)
a) 5x +10 = 2x +x +6
a) 5x -2x -x = 6 -10
a) 2x = -4
a) x = -2

b) 12-(5x-9)=4x+3
     12 - 5x +9 = 4x +3
     - 5x -4x = 3 -9 -12
     -9x = -18
       x = 2

c) 5+3(2x+2)=6-4(x+1)

   5 + 6x +6 = 6 - 4x - 1
   6x +4x = 6 -1 -6 -5
   10x = -6
x = -6/10 = - 3/5

2014-04-09T14:01:10+02:00
Salut :)

a) 5(x+2) = 2x + (x+6)
5 x (x) + 5 x 2 = 2x + x + 6
5x + 10 = 3x + 6
5x + 10 - 3x = 6
2x + 10 = 6
2x = 6 - 10
2x = -4
x = -4/2
x = -2

b) 12-(5x-9) = 4x+3
12 - 5x + 9 = 4x + 3
21 - 5x = 4x + 3
21 = 4x + 3 + 5x
21 = 9x + 3
21 - 3 = 9x
18 = 9x
x = 18/9
x = 2

c) 5+3(2x+2) = 6-4(x+1)
5 + 3 x 2x + 3 x 2 = 6 - 4 x (x) - 4 x 1
5 + 6x + 6 = 6 - 4x - 4
11 + 6x = 2 - 4x
11 + 6x + 4x = 2
11 + 10x = 2
10x = 2 - 11
10x = - 9
x = -9/10

J'espère t'avoir aidé(e) ! :)